Relación del estado nutricional con la sarcopenia en adultos mayores del sector Distrital Febres Cordero Centro de Salud #13 – Guayaquil. Noviembre 2023 – abril 2024. - Gaibor Valverde, Andrés Jesús (2024)
The aging process is different for each person according to the social, educational, cultural and economic conditions they go through. Older adults with malnutrition, whether due to a deficiency or excess of nutrients, are more susceptible to suffering from chronic diseases that affect their quality of life. Objective: Determine the relationship between nutritional status and sarcopenia in older adults in the Febres Cordero Health Center district sector #13 – Guayaquil. Methodology: this research is field, descriptive and observational established from nutritional screening methods; Sarc – F and MNA applied to 78 older adults seen in the nutrition consultation at Health Center #13, subsequently a database was created that allowed for the relationship between nutritional status and the level of sarcopenia present in adults. greater. Results: The study sample consisted of 78 older adults, of which 54% (n=42) were female and 46% (n=36) were male. Older adults within the age range of 70 to 80 years predominated with 47.44% (n=37). With a predominance of chronic non-communicable diseases (DM2 – HTN) with 64.09% (n=50) of the studied population. Nutritional status was related to the level of sarcopenia, resulting in 35.9% (n=28) of adults with sarcopenia, of which the female sex predominated with 19.23% (n=15). Conclusions: The relationship between the nutritional status and the level of sarcopenia of the elderly in the Febres Cordero district sector, Centro de Salud #13 – Guayaquil, was determined, where primary level sarcopenia was identified in a total of 28 (36%) elderly adults. with sarcopenia of which 18 (23.08%) presented malnutrition and with this the relationship of nutritional status with the presence of sarcopenia in the elderly is verified.